(untitled) (Revista de Letras, 2018)
The prose works Deutschling (1985) and Oberkanakengeil (2003) by the German-Turkish novelist Osman Engin satirically invert reigning stereotypes against Turkish immigrants. In both works, Turkish and German act as cultural and linguistic reference systems, which are subverted through the strategy of translatory mimicry. This mimicry is an integral element of the narrative structure of Engin’s works and becomes a stylistic singularity, which unbalances the German language and undermines it in its seeming naturalness. Through a close reading of Engin’s works, the contribution aims to offer a deeper understanding of the extent and nature of the unbalancing of cultural and linguistic points of reference, which implies a deconstruction of collective identities and fi xed ideas. In addition to the metalinguistic markings in the hybridized German-Turkish interlanguage of the author, as we will show, the constant alternation between object level and meta level plays an important role in the narrative structure of the texts, resulting in the continuous consideration of the mother tongue’s signifi cance and the issue of intralingual translation.